Application of the LCM Method in Randomizing Colloid and Electrolyte Questions for Basic Chemistry Subjects at SMP N 45 Medan Based on Android - Rahmat Rizal; Frinto Tambunan; Edy Victor Haryanto; Lahmudin Sipahutar; Ika Sartika (PT FORMOSA CENDEKIA GLOBAL, 2023)
The learning process that is only guided by the teacher and textbooks greatly affects the learning outcomes of students because not all students are involved in the learning process. In providing learning materials, there are some students who will feel bored and bored in receiving teacher explanations. The problems that occur include the lack of interest in learning and the attraction of students to learning materials that are considered difficult, difficult to understand, and there are certain terms in the material. the. And from the previous mapping, it was found that some students who were less able to accept learning were still in one direction, namely by learning from teacher to student. With the application of technology that will give a touch to students through an application that is embedded in a system on Android mobile or often called a smart phone. So that the increase in learning can be assessed as effective and efficient through a Smart Phone. Apart from that, this system also provides convenience in addition to learning students are also given a test or hone their skills related to the material they understand from a topic. Where practice questions are randomized systematically using the Linear Congruent Method (LCM)